2015
DOI: 10.1016/j.ajhg.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Nonsense Mutations in KAT6A, a Lysine Acetyl-Transferase Gene, Cause a Syndrome Including Microcephaly and Global Developmental Delay

Abstract: Chromatin remodeling through histone acetyltransferase (HAT) and histone deactylase (HDAC) enzymes affects fundamental cellular processes including the cell-cycle, cell differentiation, metabolism, and apoptosis. Nonsense mutations in genes that are involved in histone acetylation and deacetylation result in multiple congenital anomalies with most individuals displaying significant developmental delay, microcephaly and dysmorphism. Here, we report a syndrome caused by de novo heterozygous nonsense mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 47 publications
11
122
0
1
Order By: Relevance
“…Related to the cerebral defects, Morf is important for regulating neural stem cells [72,73]. These findings shed some light on defects characteristic of developmental disorders due to mutations in the MOZ and MORF genes [74][75][76][77][78][79]. The phenotypes observed with these mutant mice indicate that although they are interchangeable in various molecular and cell-based studies in vitro [26,34,36], MOZ and MORF have quite distinct functions in vivo.…”
Section: Moz and Morf In Vertebrate Developmentmentioning
confidence: 88%
See 2 more Smart Citations
“…Related to the cerebral defects, Morf is important for regulating neural stem cells [72,73]. These findings shed some light on defects characteristic of developmental disorders due to mutations in the MOZ and MORF genes [74][75][76][77][78][79]. The phenotypes observed with these mutant mice indicate that although they are interchangeable in various molecular and cell-based studies in vitro [26,34,36], MOZ and MORF have quite distinct functions in vivo.…”
Section: Moz and Morf In Vertebrate Developmentmentioning
confidence: 88%
“…Importantly, two recent studies have also identified recurrent MOZ gene mutations in previously unrecognized syndromes that display intellectual disability and global developmental delay (Fig. 1B) [78,79].…”
Section: Moz and Morf In Leukemia Solid Tumors And Developmental Dismentioning
confidence: 97%
See 1 more Smart Citation
“…Heterozygous mutations in MOZ have been identified in patients with microcephaly and global developmental delay, including intellectual disability and cardiac defects (5,6). Notably, MOZ has also been shown to play important roles in cardiac septum development (78).…”
Section: Involvement Of Kat6 Hats In Human Diseasementioning
confidence: 99%
“…Lysine acetyltransferase 6 (KAT6) belongs to the MYST family and has been linked to cell cycle regulation and leukemia (2)(3)(4). In addition, mutations and misregulation of the human KAT6 genes, MOZ/MORF, have been identified in solid tumors and patients with developmental disorders (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). To gain better understanding of the roles of KAT6 HATs in human diseases, it is critical to know how their functions are regulated.…”
mentioning
confidence: 99%